Dicephalus monster in a non-descript cow - A case report - PATIL, A D; MARKANDEYA, N M; SARWADE, V B; MOREGAONKAR, S D (The Indian Journal of Animal Reproduction, 2023)
Present report records a rare case of foetal dystokia due to dicephalus monster in a non-descript cow.